Implementasi Model Glasser Dalam Pendidikan Agama Kristen Upaya Membentuk Kepribadian Siswa Menengah Pertama - Moralman Gulo; Haposan Simanjuntak; Renny Victoria Sinaga; Lastri Samosir; Rongga Uli Siaphutar; Erti L Nainggolan (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
Junior high school students are teenagers who are still growing both physically and in character. However, in the process of growth, various problems arise from teenagers in general. For example, brawls between students, skipping school, cheating, often being late for school, not doing assignments, disobedience and so on. Thus, this article aims to explain how to implement the Glasser learning model in the Christian religious education learning process as an effort to shape the personality of students at the junior high school level that reflects Christian values ​​through everyday behavior. The method used in this research is a descriptive qualitative research method with a library data approach which collects various data and facts sourced from previous research and has relevance to this article, then articles, books and internet media or websites that study related topics. All sources used can be academically accountable. The result of this paper is that students are able to become responsible, independent and virtuous individuals in accordance with Christian values, by accepting the Glasser learning model designed and carried out by Christian religious education teachers through the teaching and learning process.